Changes of the ecological environment status in villages under the background of traditional village preservation: a case study in Enshi Tujia and Miao Autonomous Prefecture - Fu Li; Huiqiong Xia; Jie Miao; Jialin Yang (Scientific Reports)
Abstract The preservation of Chinese traditional villages plays a crucial role in promoting the sustainable development of rural natural, cultural, and ecological environments. It is also a key strategy for achieving rural revitalization. Current research on traditional villages predominantly focuses on the realm of cultural landscapes, with an emphasis on preserving the cultural ecological value of these communities. In comparison, discussions on the quality of the ecological environment of villages from the perspectives of natural environment, economic environment, and the social organizational environment within regional development are relatively scarce. Our study employed GIS and RS technology and refers to the Technical Criterion for Ecosystem Status Evaluation. Several sub-indices of the ecological environment status, including the biological richness index, vegetation coverage index, water network density index, and land stress index, were selected to construct an ecological environment assessment model. This model was used to analyze the spatial–temporal changes in the ecological environment status of each county, county-level city, and traditional village within the jurisdiction of Enshi Tujia and Miao Autonomous Prefecture and its surrounding areas from 2010 to 2020. The study quantitatively evaluated the ecological environment status of each county, county-level city, and village in Enshi before and after the implementation of traditional village preservation policies. Through comparative analysis, the study revealed the impact of these policies on the natural ecological environment of the study area. The results indicated the following: (1) From 2010 to 2020, the ecological index (EI) values in the villages of Enshi Prefecture exhibited a similar trend to the EI values in the respective counties and county-level cities they are located in, although significant differences in magnitude of change were observed. (2) The EI values in the counties, county-level cities, and villages demonstrated greater variation in the latter five years of the decade (2015–2020) compared to the previous five years (2010–2015). (3) In 2020, the EI value of the villages experienced more significant changes compared to 2010, whereas the overall EI value of the counties and county-level cities showed less pronounced changes. The findings of this study suggest that the traditional village preservation policies implemented in Enshi Prefecture have both positive and negative impacts on the ecological environment of the surrounding areas of protected villages, and these impacts become increasingly evident over time. By comparing and analyzing the ecological changes in the surrounding areas of traditional villages in Enshi Prefecture with the overall ecological changes in the respective counties and county-level cities, our study employs quantitative analytical methods to delve into the impact of traditional village conservation policies on the natural ecological environment. It assesses the effects of policy implementation on the natural ecological environment of traditional villages, analyzing both the positive and negative impacts brought about by the execution of these policies, with the aim of effectively guiding the natural ecological conditions of traditional villages towards a more healthy trajectory of development.